ANALYSIS TRANSLATION STRATEGIES IN “ANTI-HERO” SONG BY TAYLOR SWIFT IN ENGLISH TO INDONESIAN LANGUAGE - Utami Rosalina; Yasri Tika Damayanti (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
Translation can be described as the activity of translating the meaning of text from one language to another or SL (source language) to TL (target language).This study focuses on the investigation of translation strategy used for Taylor Swift's song